Prevalence study on the use of antibiotics in a tertiary healthcare facility - Djordjević, Zorana; Stojković, Milica; Marković, Tijana; Marković, Vladimir; Simić, Jelena; Rakić, Violeta (Vojnosanitetski pregled, 2025)
Background/Aim. Prevalence studies, also known as cross-sectional studies, offer an effective approach for gathering high-quality data on particular health concerns. The aim of the study was to analyze the utilization of antimicrobial medications (AM) in a tertiary healthcare institution. Methods. A prevalence study on AM use was performed at the University Clinical Center Kragujevac, Serbia, in early November 2022. This research was conducted as part of the Fifth National Research Initiative and employed the standardized methodology established by the European Center for Disease Prevention and Control (ECDC). Data was collected on all patients admitted to the ward before 8 a.m. Results. Among the 567 patients included in the study, 246 received at least one AM, yielding a prevalence rate of 43.4% (95% confidence interval: 39.3–47.6). The most common indications for AM use were community-acquired infections (54.9%), followed by healthcare-associated infections (19.1%), surgical prophylaxis (20.7%), and medical prophylaxis (3.7%). Parenteral administration was the most common route for AM administration (89.6%). In 97.6% of cases, the rationale for the drug application was documented in the patient’s medical records. Third-generation cephalosporins were the most frequently utilized antimicrobial group, comprising 17.9% of usage, followed by carbapenems at 12.7%, glycopeptides also at 12.7%, and fluoroquinolones at 11.8%. According to the Access-Watch-Reserve (AWaRe) classification, antibiotics under supervision were prescribed most frequently (66.4%), followed by first-choice antibiotics (28.1%), with reserve antibiotics comprising 5.5%. Conclusion. The implementation of measures to regulate the use of AM is required to retain the efficacy of these medications in the future.